Depositional Facies Influence on Reservoir Heterogeneity in The Balikpapan Formation, Lower Kutai Basin: Insights Well Log Analysis - Wahid, Abd.; Sultan; Meutia Farida; Jamaluddin; Ryka, Hamriani (Testing Center for Oil and Gas LEMIGAS, 2026)
This The Balikpapan Formation in the Lower Kutai Basin hosts a complex assemblage of fluvial-to-deltaic reservoir facies whose heterogeneity significantly influences reservoir quality and connectivity. This study integrates well-log interpretation, electrofacies classification, and quantitative petrophysical evaluation from six wells to assess the stratigraphic controls governing reservoir distribution. Three main facies associations are identified: channelised sandstones, mouth-bar to delta-front, and prodelta. Proximal channel sands exhibit the highest porosity (18–30%) and permeability (5–40 mD), but their limited lateral continuity results in poor interwell connectivity. Mouth-bar and delta-front sands display moderate porosity (12–25%) and permeability (<1–30 mD) and form laterally extensive, sheet-like bodies that enhance reservoir connectivity under increasing tidal influence. Thick prodelta mudstones act as regionally extensive vertical seals. The stratigraphic framework is characterised by repeated upward- coarsening parasequences bounded by marine flooding surfaces, reflecting alternating phases of delta progradation and transgression. These results demonstrate that depositional processes and stratigraphic architecture are the primary controls on reservoir heterogeneity in the Lower Kutai Basin.